Hubungan Kemampuan Sintaksis dengan Reading Comprehension pada Anak Gangguan Pendengaran di Surakarta - Nur Islamiati, Ulfa; Sudrajad, Kiyat (Jurnal Terapi Wicara dan Bahasa, 2023)
Abstract Background: Children with hearing impairment delays in aspects of language, one of which is written language. One of the most difficult written languages to mastered is reading comprehension. Low reading comprehension ability is often associated with low syntax ability. Sentences contained in a reading are quite complex which requires syntactical skills in reading comprehension. Objective: This research aim for knowing exists relationship between syntax ability and reading comprehension of hearing impairment children in Surakarta. Method: This research use quantitative research with cross-sectional data collection. Technique sample used on this research is purposive sampling with 30 respondens. The statistical test used is the Spearman Rank test. Results: The results of this study indicate a significance value (ρ) of 0.007 so that there is syntactic ability with reading comprehension in children with hearing loss in Surakarta. The strength indicates a correlation coefficient (r) of 0.481 which means that having a moderate category of correlation strength. Conclusion: There is relationship syntax ability with reading comprehension of hearing impairment children in Surakarta. Keywords : Syntax Ability, Reading Comprehension, Hearing Impairment Children